2017
DOI: 10.1017/laq.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

Consumption Consumes: Circulation, Exchange, and Value of San Pedro De Atacama Black Polished Ceramics

Abstract: Exchange goods contribute to social complexity and identity construction, but our knowledge of past practices associated with the circulation and consumption of such goods is limited. We explore the polished black ceramics of the San Pedro de Atacama oasis in northern Chile, which were widely traded during the first seven centuries A.D. In particular, we consider the relationships established between the agricultural and pastoral communities of the highland oases and the marine hunter-gatherers who inhabited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
(68 reference statements)
0
12
0
6
Order By: Relevance
“…This economic system was successful for several hundred years because diet was complemented by shellfish and fish brought from the Pacific coast, which implied that these goods were transported ~70 to 80 km inland (Uribe et al, 2015). Reliance on llama ( Lama glama ) caravans for facilitating interregional exchange between coastal, interior, and highland communities became increasingly important, and temporary camps are often found in association with in-stream wetlands and springs distributed along the desert (Gallardo et al, 2017). This suggests the ancient communities of the Atacama Desert were optimizing the use of all available hydrologic resources.…”
Section: Regional Synthesismentioning
confidence: 99%
“…This economic system was successful for several hundred years because diet was complemented by shellfish and fish brought from the Pacific coast, which implied that these goods were transported ~70 to 80 km inland (Uribe et al, 2015). Reliance on llama ( Lama glama ) caravans for facilitating interregional exchange between coastal, interior, and highland communities became increasingly important, and temporary camps are often found in association with in-stream wetlands and springs distributed along the desert (Gallardo et al, 2017). This suggests the ancient communities of the Atacama Desert were optimizing the use of all available hydrologic resources.…”
Section: Regional Synthesismentioning
confidence: 99%
“…It is a fact that pre-Colombian communities in the Atacama coast were in close contact with this inland oasis, as well as with other groups that inhabited the inland valleys territories since remote times [142][143][144][145][146][147]. The traditional Andean model has placed in a prominent position the trade with foreign regions and the products and technologies from abroad, from territories beyond the Andes mountain to the east, while to the coastal gatherer-hunters have been assigned a passive role in the regional economies.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, this proposed division can be used to generate a series of structuring questions by which future work could be guided, for instance by examining whether various embodied social phenomena (inequality, body use, diet), or indeed the stylistic dimensions of a myriad of material culture, change between these proposed phases. Indeed, previous studies already have identified shifts in the production of certain ceramic styles (Stovel 2013, the disappearance of the Rojo Pulido style) or the diminution of San Pedro as a ceramic production center (Gallardo et al 2017) in the century between 600-700 cal AD. The robustness of this possible moment of transition deserves examination across a broader range of artifacts and archaeological data.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the periodization of San Pedro's prehistory is tied not only to local developments but also to the role the oases played in the larger context of social developments in the region. Throughout its prehistory, the oases were an important node on the trade network that connected the region, through which passed goods and influence of the large polities that shaped the region's development, and from which flowed locally manufactured goods of regional importance (e.g., Núñez and Dillehay 1995;Llagostera 1996;Gallardo et al 2017). In this context, San Pedro de Atacama's Middle Period (AD 400-1000) has been of particular scholarly interest due to the wide distribution of characteristic goods from this period of the oases throughout the region.…”
mentioning
confidence: 99%